Unfreezing without Refreezing Change Management: Dilemmatic Roles of Agents in Succeeding the Bureaucracy Reform - Eko Prasojo; Miranda Putri; Desy Hariyati (Otoritas : Jurnal Ilmu Pemerintahan, 2021)
The implementation of bureaucracy reform in many countries continues to experience various problems, in relation to the system, regulations and actors. The success of such reform shows the important role of the actors involved in promoting change agendas. Studies on bureaucracy reform have covered many aspects of the system, stages and factors that influence its success or failure. This study specifically analyses the aspect of the related actors, namely the role of change agents in the implementation of change management, who support the implementation of bureaucracy reform. Departing from theory regarding the role of agent of change and the stages of change management during the process of bureaucracy reform, the data collection was conducted through in-depth interviews with a number of stakeholders of National Development Planning Agency, Indonesia.  The qualitative data is processed using the Discourse Network Analyzer. The results show that there are three roles conducted by the agent of change in pushing reform agendas, namely as catalysts, solution givers and as process helper. To improve the performance of their roles, there are at least two attributes that they must have, i.e., skills and behavioral attributes, which both play a significant role in supporting the success of bureaucracy reform.